Left ventricular end-diastolic pressure predicts in-hospital outcomes in takotsubo syndrome. Issue 6 (1st July 2021) - Del Buono, Marco Giuseppe; Montone, Rocco Antonio; Meucci, Maria Chiara; La Vecchia, Giulia; Camilli, Massimiliano; Giraldi, Luca; Pedicino, Daniela; Trani, Carlo; Sanna, Tommaso; Galiuto, Leonarda; Niccoli, Giampaolo; Crea, Filippo
Abstract: Aims: Takotsubo syndrome (TTS) is associated to serious adverse in-hospital complications. We evaluated the role of invasively assessed left ventricular end-diastolic pressure (LVEDP) for predicting in-hospital complications in TTS patients compared to the most widely used echocardiographic parameters of ventricular function. Methods and Results : We prospectively enrolled 130 patients (mean age 71.2 ± 11.3 years, 114 [87.7%] female) with TTS. Invasive measurement of LVEDP was performed at the time of cardiac catheterization. The rate of in-hospital complications (composite of acute heart failure, life-threatening arrhythmias and all-cause death) was examined. In-hospital complications occurred in 37 (28.5%) patients. Patients who experienced in-hospital complications had a higher prevalence of neurological trigger and lower prevalence of emotional trigger, higher LVEDP and mean E / e ′ ratio and lower LV ejection fraction (LVEF) values compared to those who did not experience in-hospital complications. At multivariate logistic regression, higher LVEDP [odds ratio (OR) 1.12, 95% confidence interval (CI) [1.05–1.20], P  < 0.001] and lower LVEF (OR 0.95, 95% CI [0.91–0.99], P  = 0.011) remained independently predictors of in-hospital complications, while emotional trigger was associated to a lower risk (OR 0.24, 95% CI [0.06–0.96], P  = 0.044). The area under the curve (AUC) for LEVDP in the prediction of in-hospital events was 0.776 (95% CI [0.69–0.86], P  <0.001, with a sensitivity and specificity of 95% and 58% using a LVEDP cut-off value of 22.5 mmHg). The AUC was significantly higher for LVEDP than for E / e ′ ratio ( P  = 0.037). Conclusions : LVEDP measured at the time of catheterization may help in identifying TTS patients at higher risk of cardiovascular deterioration with relevant therapeutic implications. Graphical Abstract: